Contemporary clinical trial updates in heart failure. (July 2016) - Robinson, Monique R.; Oliveira, Guilherme H.
Abstract : Purpose of review: Heart failure is a major source of cardiovascular morbidity and mortality worldwide. The field has benefited from steady progress, and there are now multiple strategies – medical and surgical – to improve cardiovascular outcomes. The quest continues for enhanced pathophysiologic insights and therapies. Recent findings: The chosen studies highlight new ways of treating heart failure with reduced ejection fraction (HFrEF) with pharmacotherapy such as sacubitril/valsartan and explore the role of antimicrobial therapy for chronic Chagas' cardiomyopathy. The role of iron supplementation, spinal cord stimulation and gene therapy are evaluated. The treatment of heart failure with preserved ejection fraction (HFpEF) is scrutinized, and the role of nitrates is discussed. The use of left ventricular assist devices in wider populations of HFrEF patients is considered. Summary: These pivotal contemporary trials will impact bedside management. Sacubitril/valsartan's mortality benefit in HFrEF and the negative effect of nitrates in HFpEF provide novel insights. Progress with durable mechanical circulatory support and nonpharmacological approaches to heart failure management expand therapeutic options.